Review of Economics and Statistics 2023 Annual Report - Board, Editorial (The Review of Economics and Statistics, 2023)
Current Editorial Board:Pierre Azoulay, Massachusetts Institute of TechnologyOlivier Coibion, University of Texas, AustinWill Dobbie (Co-Chair), Harvard UniversityRaymond Fisman (Co-Chair), Boston UniversityBenjamin R. Handel, University of California, BerkeleyPeter Hull, Brown UniversityBrian A. Jacob, University of MichiganScott Kominers, Harvard UniversityTavneet Suri, Massachusetts Institute of TechnologyDaniel Xu, Duke UniversityRecently Retired from the Editorial Board:Kareen Rozen, Brown UniversityXiaoxia Shi, University of Wisconsin-MadisonTable 1—Manuscripts Submitted and Published, 2018–2022This table shows the trends in papers submitted and published over the past five years. The journal saw increased growth in submissions of papers from 2018 to 2020. Submission numbers remained steady from 2020 to 2021, then declined by 10% in 2022. The number of published papers increased by 25 due to the publication of three larger issues (July, September, and November 2022).Table 2—Status of Manuscripts by Year of Submission, 2018–2022This table shows the status of manuscripts submitted over the past five years. The number of papers summarily rejected remains steady, ranging from 54% to 61% of papers submitted. The percent of papers sent out for review but ultimately rejected has remained steady, ranging from 31% to 35% of papers. Acceptance rates range from 7% to 10% of papers submitted. Papers submitted in 2022 have not had enough time to reflect the final acceptance rate.Table 3—Decision Time for Manuscripts Sent to Referees for ReviewThis table reports the decision time for manuscripts sent to referees for review over the past five years. The average decision time remained steady, ranging from 82 to 95 days.Table 4—Distribution of First Decision Times by Submission YearThis table shows the distribution of decision times for all first-round paper submissions in monthly increments for the past five years. The table also reflects the improvement in the journal's decision turnaround times. In 2022, 80% of manuscripts received a decision within three months and 99% within six months.Table 5—Subject Matter of Published Manuscripts, 2022This table shows the distribution of the subject matter of papers published in 2022. Published papers covered a variety of subjects, but the most common published topics were microeconomics and macro and monetary economics. Table 1.Manuscripts Submitted and PublishedYearSubmittedPublished20181,2007020191,3306620201,6666520211,6746520221,48090Table 2.Status of Manuscripts by Year of SubmissionSubmission YearAcceptedPendingRejectedSummary RejectRevise and ResubmitWithdrawnTotal20188903737154191,2007%0%31%60%0%2%2019982410808951,3327%0%31%61%1%0%2020126255758993721,6648%2%35%54%2%0%202121634671,009104101,6741%4%28%60%6%1%2022251652483966101,4802%1%35%57%4%1%Percentages are rounded to the nearest integer. Pending manuscripts include submissions and revisions that were undergoing review as of June 5, 2023, and Revise and Resubmit manuscripts have been returned and are in the hands of the authors on that date. Summary rejections are manuscripts rejected without referee review.Table 3.Decision Time in Days for Manuscripts Sent to Referees for ReviewFractionAverageMedian75%90thNumber of PapersYearSummarily RejectedDecision TimeDecision TimePercentilePercentileSent to Referees201860%9586112149466201961%827797118517202068%8684102122765202160%8684100118657202257%9591109137649Decision times are for papers sent out for review. Percentages are rounded to the nearest integer. Data for one paper submitted in 2022 that did not have a decision when this report was compiled have been included.Table 4.Distribution of First Decision Times by Submission Year20182019202020212022Months toMonthlyCumulativeMonthlyCumulativeMonthlyCumulativeMonthlyCumulativeMonthlyCumulativeResponsePercentPercentPercentPercentPercentPercentPercentPercentPercentPercent16565606055556262585827721171762466462313851889228420861880489389712961197149454972993992994986299<199<199<1991997199<199<199<199<1998<199<199<1100<1100<11009<199<110001000100010010<199010001000100010011<110001000100010001001201000100010001000100Percentages are rounded to the nearest integer. Data for one paper submitted in 2022 that did not have a decision when this report was compiled have been included.Table 5.Subject Matter of Published Manuscripts, 2022JELSubject CategoryNumberAGeneral Economics and Teaching0BMethodology/History of Thought0CMathematical and Quantitative Methods9DMicroeconomics18EMacro and Monetary Economics12FInternational Economics6GFinancial Economics1HPublic Economics4IHealth, Education, and Welfare9JLabor and Demographic Economics7KLaw and Economics5LIndustrial Organization4MBusiness Economics0NEconomic History0OEconomic Development8PEconomic Systems0QAgricultural/Natural Resources4RUrban, Rural, and Regional Economics1ZMisc. and Special Topics1Derived from JEL codes reported for each manuscript for the 2022 publication year.